In Silico Evaluation of the Anti-obesity and Hepatoprotective Potential of Epigallocatechin-Gallate (EGCG) and L-Theanine from Green Tea (Camellia sinensis) - Muhammad Raihan Hafizh; Syifa, Dede Syifa Izzatul Aulia (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Background: Obesity is a multifactorial disease characterized by excessive accumulation of body fat. More than 1 billion people worldwide live with obesity, as 1 in 8 deaths of non-communicable diseases are caused by obesity in 2024. The primary objective of obesity management is to improve conditions and reduce the risk of developing comorbidities through lifestyle management combined with pharmacotherapy. The only accepted pharmacological treatment from the Food and Drug Administration (FDA) is orlistat. However, there are popular alternatives by utilizing compounds in green tea (Camellia sinensis). Method: In silico analysis on EGCG and L-Theanine compounds found in Camellia sinensis were conducted to determine the feasibility of both compounds as alternatives pharmaceuticals candidates in managing obesity with hepatoprotective function using molecular docking techniques. Results: The molecular docking result demonstrated EGCG’s affinity on PPAR?, the target receptor in standard drug orlistat, exhibited higher binding affinity compared to orlistat’s affinity on PPAR?. Additionally, docking of L-Theanine compound with PI3K protein showed functional activation of PI3K by L-Theanine as one of the primary hepatoprotective pathways. Discussion: Higher binding affinity of EGCG through molecular docking indicates superior anti-obesity activity compared to standard drug orlistat. Hepatotoxicity side effects of EGCG can be mitigated by L-Theanine, which activates PI3K/Akt-NRF2, a hepatoprotective mechanism. Conclusion: In silico analysis revealed potential benefits on two compounds in Camellia sinensis, EGCG and L-Theanine. Combination of both compounds can be perceived as a new opportunity in development of obesity therapy with better therapeutic effects and safer hepatic protection.